Entwicklung eines Editors zur Erstellung und Bearbeitung Pflegerischer Informationsobjekte (PIOs) zur Pflegeüberleitung - Regner, Matthias; Werlitz, Viktor; Kleybolte, Lukas; Mess, Elisabeth Veronika; Balic, Sabahudin; Daufratshofer, Lisa; Tilmes, Sabrina; Mahler, Andreas; Heidegger, Phillip; Reuter, Claudia; Teynor, Alexandra (GMS Medizinische Informatik, Biometrie und Epidemiologie)
Standardization and digitalization of the care transmission process in Germany can help to relieve the burden on nursing staff because manual work steps can be automated. The implementation and testing of the new PIO-ULB (care information object – nursing summary, German: Pflegerisches Informationsobjekt – Überleitungsbogen, XML based FHIR bundle) in form of a PIO-ULB Editor should make the suitability of the format for a digital transition process verifiable at an early stage and should visualize its contents. The PIO-ULB Editor is a program that can be installed locally or tried out online. A clear user interface allows the users to enter care transmission data. A standardized PIO-XML file can be generated automatically and sent to receiving facilities. The PIO-ULB Editor also enables the import, display and editing of PIO-ULB files. The PIO-ULB Editor was designed and implemented as prototype software as part of the CARE REGIO research project. This article describes the development process as well as the software architecture of the editor and thus provides a basis for subsequent implementations. A lessons-learned chapter explicitly addresses potential improvements for subsequent PIO software.